Naringin attenuates inflammatory injury to the bovine endometrium by regulating the endoplasmic reticulum stress–PI3K/AKT–autophagy axis - Lu, Zihao; Peng, Qingyang; Hu, Ruiting; Wang, Yan; Fan, Kewei; Zhang, Tao (Frontiers in Pharmacology, 2024)
The occurrence of endometritis seriously affects maternal reproductive health and fertility. Natural compounds have the characteristics of high efficiency and low residue in disease treatment. We aimed to discover and reveal the pharmacological effects of naringin on endometritis, which is widely present in food and plants on endometritis.Based on network pharmacology, potential targets and pathways of naringin acting on endometritis were predicted. Animal in vivo experiments were conducted to examine the inflammatory response of LPS in uterine tissue and the therapeutic effect of naringin.2 An in vitro primary bovine endometrial epithelial cell inflammation and drug treatment model was constructed. The production of ROS was measured using DCFH-DA, and the effect of naringin on LPS induced endometritis was evaluated using HE staining, realtime quantitative PCR, Western blot and Immunofluorescence Staining methods.Naringin obviously alleviated LPS-induced inflammatory injury and oxidative stress in the endometrium of mice and bovine endometrial epithelial cells (bEECs). Further, in vitro studies were carried out to reveal the potential anti-inflammatory mechanisms of naringin based on network pharmacology. We found that naringin significantly inhibited LPS stimulated endoplasmic reticulum stress (ERS) related gene and proteins expression, thus reducing unfolded protein response (UPR). Furthermore, treatment of naringin attenuated the autophagic flux induced by ERS. Further study, we observed that PI3K/AKT pathway inhibitors or ERS inducers partially reverse the inhibition of autophagy and cell apoptosis by naringin.It is demonstrated that naringin suppressed autophagy by directly inhibited ERS-PI3K/AKT axis, exerting anti-inflammatory and antioxidant in endometritis. These findings provide novel insights into the pathogenesis of endometritis, highlighting potential therapeutic targets of traditional herbs and compounds.